The Triterpenoid CDDO-Methyl Ester Reduces Tumor Burden, Reprograms the Immune Microenvironment, and Protects from Chemotherapy-Induced Toxicity in a Preclinical Mouse Model of Established Lung Cancer - Jessica A. Moerland; Karen T. Liby (MDPI AG, 2024)
NRF2 activation protects epithelial cells from malignancy, but cancer cells can upregulate the pathway to promote survival. NRF2 activators including CDDO-Methyl ester (CDDO-Me) inhibit cancer in preclinical models, suggesting NRF2 activation in other cell types may promote anti-tumor activity. However, the immunomodulatory effects of NRF2 activation remain poorly understood in the context of cancer. To test CDDO-Me in a murine model of established lung cancer, tumor-bearing wildtype (WT) and Nrf2 knockout (KO) mice were treated with 50-100 mg CDDO-Me/kg diet, alone or combined with carboplatin/paclitaxel (C/P) for 8-12 weeks. CDDO-Me decreased tumor burden in an Nrf2-dependent manner. The combination of CDDO-Me plus C/P was significantly (p < 0.05) more effective than either drug alone, reducing tumor burden by 84% in WT mice. CDDO-Me reduced the histopathological grade of WT tumors, with a significantly (p < 0.05) higher proportion of low-grade tumors and a lower proportion of high-grade tumors. These changes were augmented by combination with C/P. CDDO-Me also protected WT mice from C/P-induced toxicity and improved macrophage and T cell phenotypes in WT mice, reducing the expression of CD206 and PD-L1 on macrophages, decreasing immunosuppressive FoxP3+ CD4+ T cells, and increasing activation of CD8+ T cells in a Nrf2-dependent manner.